Analisis Perbandingan Konsep Pendidikan Islam dan Barat - Hidayat, Amirul; Dede Rosyada (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This paper presents a comparative analysis of Islamic and Western concepts, focusing on their philosophical, cultural, and social dimensions. The study examines the underlying principles and values that shape each conceptual framework, highlighting similarities, differences, and areas of convergence. Through a comprehensive review of literature and historical perspectives, the paper explores key themes such as ethics, governance, justice, and human rights within both Islamic and Western traditions. Additionally, the analysis delves into the influence of historical events, religious beliefs, and cultural norms on the development and interpretation of these concepts in each tradition. By critically examining the similarities and differences between Islamic and Western concepts, this study aims to contribute to a deeper understanding of the diverse philosophical and cultural perspectives that shape global discourse and facilitate dialogue between different civilizations.